People versus Machines: The Impact of Minimum Wages on Automatable Jobs - Grace Lordan; David Neumark (Institute of Labor Economics (IZA), 2018)
We study the effect of minimum wage increases on employment in automatable jobs – jobs in which employers may find it easier to substitute machines for people – focusing on low-skilled workers for whom such substitution may be spurred by minimum wage increases. Based on CPS data from 1980–2015, we find that increasing the minimum wage decreases significantly the share of automatable employment held by low-skilled workers, and increases the likelihood that low-skilled workers in automatable jobs become nonemployed or employed in worse jobs. The average effects mask significant heterogeneity by industry and demographic group, including substantive adverse effects for older, low-skilled workers in manufacturing. We also find some evidence that the same changes improve job opportunities for higher-skilled workers. The findings imply that groups often ignored in the minimum wage literature are in fact quite vulnerable to employment changes and job loss because of automation following a minimum wage increase.
Keywords: J23; J38; 330; minimum wage; employment; automation